Challenges encountered in maintaining mobile early childhood care and education centres: Practitioners’ perspectives - Ugwuanyi, Christian S; Okeke, Chinedu C (Aṭfālunā Journal of Islamic Early Childhood Education, 2024)
This research aims to examine the challenges faced by practitioners who maintain mobile Early Childhood Care and Education (ECCE) centers. Using a qualitative approach, ten practitioners from one organization that provides mobile ECCE in the Free State Province participated in this study. A semi-structured interview guide was used for data for this study. ATLAS.ti software was used to analyze qualitative data. The findings showed that the language barrier is one of the greatest challenges presented by mobile ECCE programs. Further, psychosocial challenges, such as the abuse of alcohol by parents and poverty as well as rain and wind, dust and cold are also challenges to practitioners. Therefore, these findings have strong policy implications for the need for ECCE policy frameworks to mitigate language barriers and psychosocial challenges in mobile ECCE centers by knowing the different home languages of the children.